IDENTIFICATION OF THE HARD LAYER USING WENNER CONFIGURATION RESISTIVITY METHOD (CASE STUDY: JALAN SAMBOJA – SEPAKU) - Febrian Dedi Sastrawan; Liliana Rossa; Rahmania Rahmania; Meidi Arisalwadi; Adrian Rahmat Nur (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2023)
Samboja – Sepaku road is a land transportation route that can be used from the cities of Balikpapan and Samarinda to the new capital city. There is a problem with this road. Namely cracks appear on several roads due to subsidence. This is because the layer of soil that supports this road is thick and has young sediment. The hilly topography and steep ravines that dominate this road area also contributed to the subsidence. Efforts that can be made to deal with the occurrence of land subsidence are geotechnical engineering, such as making siring. In the construction process, the siring foundation must be planted in a dense layer of soil that is not easily shifted or unstable, which is also known as a hard layer. Determining the position of the hard layer can be done by identifying the subsurface stratigraphy using the resistivity method. The results of the subsurface lithology depiction obtained two types of soil layers that dominate the roadside area, namely clay layers with resistivity values of 2.31 Ωm – 15.1 Ωm and sandy clays with resistivity values of 38.7 – 253 Ωm. The clay layer is the recommended layer as a hard layer at a depth of 15-20 meters.